2019
DOI: 10.1136/bmjopen-2018-023233
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rheumatoid arthritis in relation to serum cadmium concentrations: cross-sectional study using Korean National Health and Nutrition Examination Survey (KNHANES) data

Abstract: ObjectivesIt has been suggested that exposure to heavy metal cadmium (Cd) may contribute to a high risk of developing rheumatoid arthritis (RA). This study was to investigate the association of RA prevalence and serum concentrations of Cd and other heavy metals through large survey data analysis.DesignA retrospective cross-sectional survey study.SettingLarge population survey in Korea.Participants53 829 subjects participated in Korean National Health and Nutrition Examination Survey (KNHANES) from 2008 to 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Conversely, administration of hormones such as oral contraceptives, which contain progesterone and oestrogen, seems to increase serum copper and ceruloplasmin levels in humans and rats, while hepatic zinc stores are elevated [ 83 ]. In a large cross-sectional study of the Korean National Health and Nutritional Examination Survey, RA in females was associated with increased cadmium in sera [ 84 ]. Cadmium can be an endocrine disruptor and considered a “metallo-oestrogen” because of its oestrogenic actions.…”
Section: Zinc and Cadmium In The Aetiology And As Risk Factors Of mentioning
confidence: 99%
“…Conversely, administration of hormones such as oral contraceptives, which contain progesterone and oestrogen, seems to increase serum copper and ceruloplasmin levels in humans and rats, while hepatic zinc stores are elevated [ 83 ]. In a large cross-sectional study of the Korean National Health and Nutritional Examination Survey, RA in females was associated with increased cadmium in sera [ 84 ]. Cadmium can be an endocrine disruptor and considered a “metallo-oestrogen” because of its oestrogenic actions.…”
Section: Zinc and Cadmium In The Aetiology And As Risk Factors Of mentioning
confidence: 99%
“…At first glance it seem unlikely that mercury is responsible for this link since only a small amount of mercury is present in cigarette smoke (39). However, the large amount of cadmium in cigarette smoke (40) may be relevant, since cadmium exposure is a proposed risk factor for rheumatoid arthritis (41), and synergistic actions between toxic metals such as cadmium and mercury are recognized (42). Cadmium and mercury from cigarette smoke could therefore accentuate each other's toxicity within the synovium.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain more evidence that toxic metals could trigger connective tissue diseases, further studies using this toxicant model could be combined with strains of mice that are genetically susceptible to develop an autoimmune reaction to mercury (21), with mice exposed to cigarette smoke (38), or with mice on a low selenium diet which could potentiate mercury toxicity (85). In addition, other metal toxicants such as lead (86) and cadmium (41) could be studied for their effects on connective tissues. In the case of osteoarthritis, this toxicant model could be used to see if osteoarthritis develops earlier than expected in genetic strains of mice who develop spontaneous osteoarthritis or obesity, or in mice who have a destabilized medial meniscus to predispose them to osteoarthritis (51).…”
Section: Discussionmentioning
confidence: 99%
“…Cd is an environmental pollutant that is dangerous to health, and according to Hutchinson (2015), smoking is the main source of Cd. The main studies about the effect of Cd on the osteoarticular system are related to osteomalacia, osteoporosis, rheumatoid arthritis (RA), and OA (Hutchinson, 2015; Joo et al, 2019; Kamiński et al, 2018; Reyes-Hinojosa et al, 2019). Studies in osteoblast cell lines indicate that Cd toxicity is related to its capacity of being absorbed and accumulating in the cells (Lévesque et al, 2008; Smith et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cd can also cause peptide citrullination, a process that has been associated as part of RA development (Hutchinson, 2015). Joo et al (2019) demonstrated that RA patients have increased Cd levels (1.30 mg/L) in blood, associating it with RA risk.…”
Section: Introductionmentioning
confidence: 99%